Psychological insulin resistance among type 2 diabetic patients attending primary healthcare centers, Al-Ahsa, Saudi Arabia - Asmaa M Alomran; Duaa A Almubarak; Batool A Alrashed; Abdul S Khan (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Patients' adherence to insulin therapy is crucial to achieve good glycemic control. The present study was conducted to determine psychological insulin resistance (PIR) and the effect of doctor-patient relationship on PIR among type 2 diabetes patients attending primary health-care centers of Al-Ahsa region in Saudi Arabia. MATERIALS AND METHODS: This was a cross-sectional survey of all type 2 diabetic patients attending the primary healthcare centers of Al-Ahsa. A multistage sampling technique was used. The calculated sample size was 396. Two validated structured questionnaires were used to collect information. The degree of agreement to insulin therapy was done on the Likert 5° scale. SPSS was used for data entry and analysis. Chi-square test was used to test for stistical significane at P=0.05. RESULTS: Out of 396 patients who were given the questionnaires, 366 filled the questionnaires yielding 92% response rate. Fifty-one percent were male and about 85% were older than 35 years. Willingness to use insulin was significantly associated with age (P = 0.013) and duration of diabetes (P=0.0001). The strongest negative attitudes toward insulin therapy arose from participants having heard about a bad experience with insulin (59.34%, P < 0.05) and the fear of possible dependence (54.20%, P < 0.05). Participants who responded of "mostly appropriate" and "very appropriate" to questions on patient-doctor relationship were significantly more willing to take insulin (64.9% vs 24.5%, and 70.3% vs 22.9%, P = 0.0001). CONCLUSION: The study showed that one-third of the patients with type 2 diabetes had PIR. Since the behavior of doctor plays an important role in reducing PIR, there is a need for greater emphasis on the importance of good doctor-patient relationship and the establishment of a therapeutic education program.